Investigating Scuba Divers' Attitudes To Sustainable Shipwreck Diving In North Carolina - Duncan, James P. (East Carolina University, 2015)
This study examined the ways in which NC scuba divers identify sustainable shipwreck diving activities to gain a better understanding of how their behavior impacts sustainable cultural tourism on the coast of North Carolina. The information collected by this study revealed the norms of respondents regarding how human activities affect the sustainability of submerged maritime archaeological sites. This was done by comparing diver characteristic variables in relation to attitudes regarding a multitude of sustainable shipwreck diving activities as they were defined by previous literature (Stone 1996; McCarthy 2000; Jewell 2004; Edney 2006). Results concluded that divers that belong to archaeological organizations tended to define sustainable diving activities as the literature does. The most experienced divers not a member of these groups tend to disagree with the literature when it comes to identifying sustainable diving activities.
Keywords: Recreation; Tourism; Scuba diving--North Carolina; Scuba divers--North Carolina; Recreational dive industry--North Carolina; Sustainable tourism--North Carolina; Underwater archaeology--North Carolina; Shipwrecks--North Carolina